Preparation method of low-load ruthenium-based catalyst for biogas dry-wet dual preparation of hydrogen-suitable mixed gas

By using soft template agents to assist in the preparation of low-load high-dispersion catalyst Ru/MgO-ST in the wet and dry reaction of biogas, the problem of easy agglomeration of high-loaded ruthenium-based catalysts at high temperatures is solved, and the effect of efficient conversion of biogas to synthesis gas is achieved, and the cost of catalyst is reduced.

CN117563587BActive Publication Date: 2025-03-21SOUTH CHINA AGRICULTURAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311553766.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-11-15
Filing Date
2023-11-20
Publication Date
2025-03-21
Estimated Expiration
2043-11-20

AI Technical Summary

Technical Problem

The high-supported ruthenium-based catalysts used in the existing biogas wet and dry dual reforming reaction are prone to agglomeration at high temperatures, with limited catalytic performance and high cost, so they cannot be suitable for large-scale industrial production.

Method used

By using soft template agents to assist in the preparation of low load and high dispersion biogas wet and dry double-forming catalyst Ru/MgO-ST, the low load and high dispersion of biogas, using porous MgO as a support, Ru is loaded on the porous MgO surface in a highly dispersed state, avoiding the agglomeration of the catalyst at high temperatures, and improving catalytic performance and resource utilization.

Benefits of technology

A high conversion rate of biogas is achieved, and the hydrogen-carbon ratio is as high as 90%, and the hydrogen-carbon ratio is about 2. It is suitable for industrial production and reduces the cost of catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117563587B_ABST
    Figure CN117563587B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a low-load ruthenium-based catalyst for a biogas dry-wet dual-process hydrogen-adapted mixed gas. The method uses different soft template agents to assist and optimize the active metal loading, so that the Ru particles are small, highly dispersible, and evenly dispersed, and a low-load, efficient, and stable ruthenium-based catalyst is obtained, which avoids the problem that the catalyst is easy to agglomerate at high temperatures and the catalytic performance is limited; at the same time, by reducing the noble metal loading, the catalyst cost is reduced and the resource utilization rate is improved. The catalyst Ru / MgO-ST prepared by the method has a conversion rate of up to 90% in catalyzing the dry-wet dual-process conversion of biogas to synthesis gas methane, and the hydrogen-carbon ratio (H2 / CO) of the converted gas is about 2, which can well catalyze the dry-wet dual-processing of biogas to hydrogen / alcohol mixed gas, which makes it a promising candidate material for the preparation of green hydrogen / biomethanol, and its process is simple, low cost, and easy to promote industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts, and more specifically, relates to a method for preparing a low-load ruthenium-based catalyst for a biogas dry-wet dual-process hydrogen-suitable mixed gas. Background Art

[0002] With the progress of global industrialization and social civilization, human demand for energy continues to increase. However, the main energy supply of today's society still relies on non-renewable fossil fuel resources such as coal, oil and natural gas. With the acceleration of globalization and population growth, the earth's resources are overexploited and consumed, especially non-renewable resources. Although there are still resources such as deep-sea oil and gas, methane hydrate, coalbed methane and shale gas available for development and utilization, humans have gradually realized the potential shortage of non-renewable fossil fuels and turned to renewable energy. Furthermore, the excessive use of fossil fuels will lead to a continuous increase in the concentration of carbon dioxide in the atmosphere, which will have a huge negative impact on the climate and ecological balance. With the increasing awareness of environmental protection in recent years, how to reasonably use carbon dioxide that causes the greenhouse effect has also become one of the issues of global concern.

[0003] As a renewable green clean energy, biogas has attracted much attention in recent years because of its widespread presence in nature and its environmentally friendly advantages. Compared with coal and oil, biogas emits fewer harmful gases; and in the long run, with the development of biogas utilization technology, it has the potential to become the main chemical raw material to replace oil in the 21st century. Therefore, as the third largest energy source, replacing oil with gas has become the trend of future energy and chemical raw material development. Biogas is a clean and easy-to-transport energy substance. It is rich in natural gas such as methane and carbon dioxide. In addition to being used directly as a clean energy source, biogas can also be prepared into chemical raw materials after processing. For example, biogas steam catalytic conversion can produce synthesis gas for the manufacture of various hydrocarbons and oxygen-containing derivatives, such as agricultural chemicals and melamine. In addition, biogas can also be converted into pure hydrogen to support other industries. According to statistics, about 100 million tons of methane are emitted into the atmosphere through various channels every year, of which about half is produced by human activities; and carbon dioxide is the most common greenhouse gas in the atmosphere. Therefore, the rational and effective development and utilization of methane and carbon dioxide in biogas has a dual significance. It can not only effectively utilize resources, but also control the greenhouse effect produced by methane and carbon dioxide and reduce its impact on global warming.

[0004] Synthesis gas is a high-concentration mixed gas composed of carbon monoxide and hydrogen, with a molar ratio of CO to H2 between 1 / 2 and 3 / 1. Synthesis gas is one of the important raw materials for chemical organic synthesis. It is widely used in the chemical industry and production fields. Various carbon-containing resources, such as coal, natural gas, petroleum and residual oil, can be used to produce synthesis gas. Synthesis gas can be converted into liquid fuels, gaseous fuels, bulk chemicals and high-value-added fine organic chemical products. Therefore, it is of great significance to use renewable biogas as a raw material to replace synthesis gas, which can effectively reduce environmental pollution and greenhouse effect. For the technology of methane conversion to synthesis gas, the existing technology generally adopts methods such as methane partial oxidation method, methane autothermal conversion method or methane catalytic partial oxidation method.

[0005] Biogas dry-wet double whole reaction is a new synthesis gas preparation technology that directly converts two major greenhouse gases (methane and carbon dioxide) into synthesis gas. Since it was proposed, it has made great progress, but it still faces great challenges in technology, especially in the preparation of catalysts. In the biogas dry-wet double whole reaction, the main technical core is the preparation of catalysts, which need to contain carriers, additives, active component dispersion and other contents. In the catalytic conversion of biogas dry-wet double whole to synthesis gas for the synthesis of biomethanol, precious metal catalysts such as palladium (Pd), platinum (Pt) and ruthenium (Ru) are currently widely used. These precious metal catalysts have excellent catalytic activity and excellent catalytic effect, but they are expensive and inconvenient to recycle, with poor practicality and cannot be applied to large-scale industrial production. Furthermore, existing studies have shown that high-load ruthenium-based catalysts with Ru as the active component have the disadvantages of easy aggregation and sintering of the active component at high temperature, and limited catalytic performance. In addition, problems such as catalyst agglomeration and coking often occur in industrial applications, which deactivates the active component on the carrier due to the shell-like carbon isolation layer formed by aggregation; in addition, the active component ruthenium will form ruthenium oxide after oxidation, resulting in a large area of ​​​​the loss of catalytic activity. Therefore, how to develop a catalyst with low cost, stable performance and good catalytic effect is a problem that needs to be solved urgently in the field of synthesis gas preparation. Summary of the invention

[0006] The purpose of the present invention is to overcome the above-mentioned defects and shortcomings in the prior art and to provide a method for preparing a low-loaded ruthenium-based catalyst for a biogas dry-wet dual-process hydrogen-suitable mixed gas.

[0007] The above-mentioned object of the present invention is achieved through the following technical solutions:

[0008] In order to solve the above problems, the present invention provides a low-load, highly dispersed biogas dry-wet dual-process catalyst Ru / MgO-ST and a preparation method thereof after a large number of experimental studies. The catalyst uses alkaline oxide as a carrier and Ru as a catalytically active component. By using different soft template agents to assist and optimize the active metal loading, the Ru particles are small, highly dispersed, and evenly dispersed, thereby obtaining a low-load, highly efficient, and stable ruthenium-based catalyst, which avoids the problem that the catalyst is easy to agglomerate at high temperatures and the catalytic performance is limited; at the same time, by reducing the loading of the precious metal Ru, the catalyst cost is reduced and the resource utilization rate is improved. The catalyst provided by the present invention has a high conversion rate and can well catalyze the dry-wet dual-processing of biogas to produce hydrogen / alcohol mixed gas, that is, synthesis gas, which can be used for industrial synthesis of biomethanol / hydrogen.

[0009] Therefore, the present invention first provides a method for preparing a low-loaded and highly dispersed biogas dry-wet dual-catalyst Ru / MgO-ST, wherein the Ru / MgO-ST is prepared by the following steps:

[0010] S1: Mix the ruthenium source, magnesium source and soft template source and treat them by mechanochemical method for 2 to 12 hours;

[0011] S2: calcining the Ru / MgO-ST precursor at 500-700° C. for 4-6 hours in an oxygen-containing atmosphere to obtain Ru / MgO-ST.

[0012] Studies have shown that high-loaded ruthenium-based catalysts with Ru as the active component have the disadvantages of easy aggregation and sintering of the active component at high temperature and limited catalytic performance. In addition, catalyst agglomeration and coking often occur in industry, resulting in the deactivation of the catalyst due to the formation of a shell-like carbon isolation layer caused by the aggregation of the active component on the carrier. In addition, the catalytic activity of ruthenium oxide formed by oxidation of the active component ruthenium also leads to large-scale deactivation of the catalyst. Therefore, the present invention optimizes the high-loaded ruthenium-based catalyst from two aspects of the carrier and the catalyst active component.

[0013] On the one hand, the present invention uses MgO with face-centered cubic closest packing as the carrier of the catalyst, and disperses the MgO molecules by high-temperature calcination, providing a larger attachment site for the active component, and the soft template agent confines it in the carrier to prevent the sintering of the active component due to aggregation. On the other hand, the soft template agent can be combined with MgO to form a complex or coprecipitation system. Through the subsequent calcination treatment, the soft template agent will be pyrolyzed or volatilized, and thus completely removed. The removal of the soft template agent will leave a pore or pore structure, which can increase the specific surface area of ​​the catalyst, increase the contact area between the reactant molecules and the catalyst, and enhance the reaction activity. Therefore, the soft template method realizes the high dispersion of the active metal Ru and the porous structure of the porous MgO, providing more surface sites and contact opportunities, thereby significantly improving the activity and reaction efficiency of the catalyst. The mechanochemical method further reduces the size of the active metal Ru particles and increases the interface area between the reactant and the catalyst. In addition, the stability and anti-aggregation properties of the porous MgO help to extend the life of the catalyst. The present invention also orderly disperses the ruthenium element in Ru / MgO-ST prepared by the soft template-assisted mechanochemical method, so that the ruthenium particles are small, highly dispersible, and evenly dispersed, thereby obtaining a low-loaded and highly dispersed ruthenium-based catalyst, avoiding the problem that the existing high-loaded ruthenium-based catalyst is easy to agglomerate at high temperature and has limited catalytic performance.

[0014] Furthermore, the ruthenium source in S1 is one or more of ruthenium acetate, ruthenium chloride, ruthenium acetate or ruthenium acetylacetonate.

[0015] Preferably, the ruthenium source in S1 is ruthenium acetate.

[0016] Furthermore, the magnesium source in S1 is one or more of magnesium acetate or magnesium nitrate.

[0017] Preferably, the magnesium source in S1 is magnesium nitrate.

[0018] Conventional ruthenium sources, magnesium sources and template sources in the art can all be used in the preparation of the biogas dry-wet dual-process catalyst Ru / MgO-ST in the present invention.

[0019] Furthermore, the template source in S1 is one or more of cetyltrimethylammonium bromide (CTAB), polyether (P123), polyetherimide (PEI), polyvinylpyrrolidone (PVP 10) or polyethylene glycol (PEG).

[0020] Preferably, the template source in S1 is CTAB.

[0021] Furthermore, the molar ratio of the ruthenium element in the ruthenium source to the alkaline metal oxide in the magnesium source is (0.05-3):(97-99.95).

[0022] Furthermore, the mass ratio of the soft template agent source to other precursor salts in the catalyst is 0.1-0.5:1.

[0023] Furthermore, the mechanochemical method described in S1 is one or more of grinding or ball milling.

[0024] Preferably, the mechanochemical method in S1 is a ball milling method.

[0025] Preferably, the ball milling beads in the mechanochemical method described in S1 are selected from one or more of zirconium balls, stainless steel balls or corundum balls.

[0026] Preferably, the ball milling beads used in the mechanochemical method described in S1 are zirconium balls.

[0027] Preferably, the mechanochemical treatment in S1 is carried out for 8 hours.

[0028] Furthermore, the mass fraction ratio of the template and other catalyst precursors in the S1 template source is 1:5.

[0029] Furthermore, the calcination temperature in S2 is 550° C. and the calcination time is 4 h.

[0030] Furthermore, the oxygen-containing atmosphere in S2 is an air atmosphere.

[0031] Furthermore, in S2, the temperature is increased at a heating rate of 5 to 10°C / min.

[0032] Preferably, the temperature is increased at a heating rate of 5° C. / min in S2.

[0033] Furthermore, the method further comprises reducing and activating the Ru / MgO-ST in a hydrogen atmosphere at 600-800° C., thereby obtaining the Ru / MgO-ST with improved catalytic performance.

[0034] The Ru / MgO-ST structure is formed to allow the ruthenium element to be distributed in a more orderly manner and form a highly ordered redox cycle. Only after hydrogen reduction can the metallic ruthenium have strong catalytic activity and stability. The distribution of the active metallic ruthenium after oxidation-reduction is more standardized and orderly, thereby enhancing the reducibility of the ruthenium element and improving the catalytic activity, and will not be affected by other factors such as agglomeration and carbon deposition.

[0035] Preferably, the reduction temperature is 600° C. and the reduction time is 2 h.

[0036] Therefore, the present invention provides a biogas dry-wet dual catalyst Ru / MgO-ST, which uses porous MgO as a carrier, and Ru is loaded on the porous MgO surface in a highly dispersed state, and the loading amount of Ru is 0.05-3%.

[0037] Preferably, the Ru loading amount is 0.2% to 2.1%.

[0038] It should be understood that the loading refers to the mass fraction of the catalytically active component Ru in the entire Ru / MgO-ST catalyst.

[0039] When the Ru / MgO-ST prepared by the present invention uses Ru as the active metal and porous MgO as the catalyst carrier, the porous MgO carrier treated by the soft template method presents multiple advantages. First, the porous structure provides more attachment sites, allowing the metal Ru to exist on the carrier surface in a highly dispersed manner, thereby improving the activity and selectivity of the catalyst. Secondly, porous MgO has a large specific surface area and an ordered pore structure, which helps to increase the contact area between the reactant molecules and the catalyst, improve the diffusivity of the reactant molecules on the catalyst surface, and improve the reaction efficiency of the catalyst. In summary, the porous MgO carrier treated by the soft template method provides the Ru-based catalyst with more attachment sites, highly dispersed active metals and good mass transfer characteristics, thereby enhancing the performance and activity of the catalyst and showing excellent performance in the catalytic reaction.

[0040] The loading amount of Ru has a certain influence on the performance of the catalyst. If the loading amount is too low, the sparse distribution of Ru cannot achieve the synergistic effect of oxidation and reduction; high loading amount of noble metals will cause waste of resources. Secondly, too high loading amount of noble metals may cause saturation effect of active sites, resulting in deactivation of some sites or inability to fully utilize them, thus reducing the activity of the catalyst. In addition, high loading amount of noble metals may also increase the risk of catalyst deactivation and reduce the stability and durability of the catalyst. By optimizing the loading amount conditions, the catalytic activity of Ru / MgO-ST can be further improved, achieving high catalysis with low loading amount.

[0041] The present invention also provides application of the Ru / MgO-ST catalyst in preparing biofuel.

[0042] Furthermore, the present invention provides the use of the above-mentioned Ru / MgO-ST catalyst in catalyzing the dry-wet dual conversion of biogas into synthesis gas. The catalytic dry-wet dual conversion of biogas into synthesis gas is Ru / MgO-ST catalyzing biogas into synthesis gas (CO and H2), and the synthesis gas can be used as a raw material for synthesizing biofuel methanol.

[0043] Therefore, the present invention also provides a method for catalyzing the dry-wet dual integration of biogas into synthesis gas using the above-mentioned catalyst Ru / MgO-ST. The method is that the catalyst Ru / MgO-ST catalyzes the dry-wet dual integration of biogas into synthesis gas at 650-800°C under normal pressure.

[0044] Preferably, the catalytic temperature is 800°C.

[0045] Furthermore, when the biogas flow rate is 80 mL / min, the amount of catalyst Ru / MgO-ST is 0.2 g.

[0046] The catalyst Ru / MgO-ST has a conversion rate of 25% to 95% in catalyzing biogas conversion to synthesize methane. At a temperature of 800°C, its methane (CH4) conversion rate is as high as 90%, and the carbon dioxide (CO2) conversion rate is 60%. The hydrogen-to-carbon ratio (H2 / CO) of the converted gas is about 2, which makes it a promising candidate material for biomethanol production.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] The present invention provides a method for preparing a low-load ruthenium-based catalyst for hydrogen-adapted mixed gas by dry-wet dual-processing of biogas. The method uses different soft template agents to assist and optimize the active metal loading, so that the Ru particles are small, highly dispersible, and evenly dispersed, and a low-load, efficient, and stable ruthenium-based catalyst is obtained, which avoids the problem that the catalyst is easy to agglomerate at high temperatures and the catalytic performance is limited; at the same time, by reducing the noble metal loading, the catalyst cost is reduced and the resource utilization rate is improved. The catalyst Ru / MgO-ST prepared by the method uses porous MgO as a carrier, and Ru is loaded on the surface of the porous MgO. The loading amount of Ru is 0.05-3%. The conversion rate of catalytic dry-wet dual-processing of biogas to syngas methane is as high as 90%, and the hydrogen-carbon ratio (H2 / CO) of the converted gas is about 2, which makes it a promising candidate material for the preparation of biomethanol. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 This is the X-ray diffraction pattern (XRD) of catalyst Ru / MgO-STX.

[0050] Figure 2 This is the EDS-Mapping diagram of Example 2.

[0051] Figure 3 Graph showing the conversion rate of methane in the reaction products of Examples 1 to 3.

[0052] Figure 4 This is a graph showing the conversion rate of methane in the reaction products of Examples 4 to 8.

[0053] Figure 5 This is a diagram showing the conversion rate of methane and carbon dioxide and the H2 / CO stability in the products of the catalytic biogas double reaction in Example 2. DETAILED DESCRIPTION

[0054] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0055] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0056] Examples 1 to 3

[0057] Examples 1 to 3 provide a series of catalysts Ru / MgO-ST, which are prepared by the following method.

[0058] Preparation of Ru / MgO-ST catalyst: Fill the ball mill with zirconia balls to a volume of one third. Then add the corresponding mass of C 14 H 21 O 15 Ru3, Mg(NO3)2·6H2O and C 19 H 42 BrN. The mixture was ground at 600 rpm in a planetary ball mill at room temperature for 8 h to obtain a Ru / MgO-ST precursor solid. The obtained Ru / MgO-ST precursor was calcined in an air atmosphere in a muffle furnace by a calcination method. The calcination heating rate was 5°C per minute, and the temperature was raised to 550°C and calcined for 4 h. After cooling to room temperature, the obtained solid was ground into powder to obtain the catalyst Ru / MgO-ST

[0059] The specific addition amount is shown in Table 1 (Ru loading amount = Ru / (Ru mass + MgO mass)).

[0060] Table 1 Preparation of 1g catalyst Ru / MgO-ST and its dosage control in Examples 1 to 3

[0061]

[0062] Embodiments 4 to 8

[0063] Examples 4 to 8 provide catalysts Ru / MgO-ST prepared with different soft templates, which are prepared according to the methods described in Examples 1 to 3. The specific addition amount of each component is shown in Table 2.

[0064] Table 2 Preparation of 1g catalyst Ru / MgO-ST and its dosage control in Examples 4 to 8

[0065]

[0066] Example 9 Performance Test of Catalyst Ru / MgO-ST

[0067] (I) Characterization

[0068] The catalysts prepared in Examples 1 to 8 above were characterized by the following means.

[0069] 1) X-ray diffraction pattern (XRD): such as Figure 1 shown.

[0070] Figure 1 The XRD patterns of the Ru / MgO-ST catalysts obtained in Examples 1 to 8 are as shown in the figure. The XRD diffraction patterns of all catalysts of the Ru / MgO-ST system show that only the peak of the carrier MgO appears, and no peak corresponding to the active metal Ru is observed, thereby confirming that the active metal Ru is successfully dispersed on the carrier MgO in this system.

[0071] 2) ICP-AES test: Table 3 shows the active metal Ru loading of the catalyst Ru / MgO-ST obtained in Examples 1 to 8. After ICP-AES test, the actual active metal Ru loading is substantially the same as the theoretical loading.

[0072] Table 3 Active metal loading of samples after calcination

[0073]

[0074] Note: Ru content was determined by ICP-AES

[0075] 3) EDS-Mapping test: Figure 2 This is the EDS-Mapping diagram of Example 2. The EDS-Mapping diagram reveals the uniform distribution of low-loaded Ru in the MgO matrix, indicating that good Ru dispersion was achieved during the preparation of the catalyst. This uniform distribution is expected to have a positive impact on catalytic activity and selectivity, improve surface availability, and provide key insights into catalyst performance and process optimization.

[0076] (II) Catalytic activity

[0077] The activity evaluation of the catalyst prepared in the above embodiment was carried out on a fixed bed reactor at normal pressure. Before the activity test, the catalyst Ru / MgO-ST (40-60 mesh, 200 mg) was pre-reduced and activated in a 10% H2 / N2 atmosphere (Ru / MgO-ST was obtained after reduction), the reduction temperature was 600°C, the reduction time was 2h, and the mass space velocity WHSV was 30600 mL·h -1 ·g cat -1 , nCH4:nCO2:nH2O:nN2=3:2:2.5:1. The gas after the reaction was detected by online gas chromatography (Panuo, A60).

[0078] Test conditions: atmospheric pressure, mass space velocity WHSV = 30,600 mL·h -1 ·g cat -1The test temperature range is 650-800℃, the temperature interval is 50℃, the temperature rate is controlled at 10℃ / min by programmed temperature rising technology, each temperature point is maintained for 1h, and the catalyst activity is expressed as CH4 conversion rate (X CH4 )express.

[0079] CH4 conversion rate (X CH4 ) is calculated as follows:

[0080] X CH4 =([CH4] in -[CH4] out ) / [CH4] in ×100%;

[0081] Where [CH4] in and [CH4] out are the CH4 contents in the raw gas and the reaction tail gas respectively. The test results are as follows: Figure 3 , Figure 4 .

[0082] like Figure 3 As shown, with the increase of reaction temperature, the CH4 conversion rates of Examples 1, 2, and 3 are all improved to varying degrees. Among them, the CH4 conversion rates of Examples 2 and 3 are close to and significantly higher than that of Example 1. When the reaction temperature is 800°C, the CH4 conversion rates of Examples 2 and 3 are both over 90%. It shows that increasing the loading of active metal Ru in the catalyst Ru / MgO-ST can increase the CH4 conversion rate of the catalyst. Since Ru is a precious metal, reducing its content in the catalyst can significantly reduce the preparation cost of the catalyst, making it more economical and feasible. Lower Ru content usually leads to smaller and more evenly dispersed Ru particles in the catalyst, which helps to improve the activity and efficiency of the catalyst. Smaller particles can provide more active surface area, thereby improving the reaction rate. The CH4 conversion rates of Examples 2 and 3 are close, but the active metal Ru loading of Example 2 is lower, so Example 2 has multiple advantages such as economy, resources and competition as a lower-cost catalyst, making it more attractive and practical in industrial and scientific research applications, and these advantages can emphasize its superiority in the field of catalysis.

[0083] like Figure 4 As shown, the CH4 catalytic activity of the catalyst obtained by using different soft template agents in the preparation of the catalyst Ru / MgO-ST is different. With the increase of the reaction temperature, the CH4 conversion rates of Examples 4, 5, 6, 7, and 8 are all improved to varying degrees. When the reaction temperature is 800°C, Example 4 shows the highest CH4 conversion rate. When the active metal Ru is added during the preparation of the catalyst, a higher CH4 conversion rate can be obtained by adding the soft template agent CTAB, and the atomic utilization rate of the active metal Ru is higher.

[0084] (III) Catalyst stability

[0085] Taking the catalyst prepared in Example 2 as an example, the stability of the catalyst was tested: The activity evaluation of the catalyst prepared in the above example was carried out on a fixed bed reactor at normal pressure. Before the activity test, the catalyst Ru / MgO-ST (40-60 mesh, 200 mg) was pre-reduced and activated in a 10% H2 / N2 atmosphere (Ru / MgO-ST was obtained after reduction), the reduction temperature was 600°C, the reduction time was 2h, the temperature program technology was used to control the heating rate to 10°C / min, and the temperature was raised to 800°C after reduction. Mass space velocity WHSV = 30600mL·h -1 ·g cat -1 , nCH4:nCO2:nH2O:nN2=3:2:2.5:1. The gas after the reaction was detected by online gas chromatography (Panuo, A60).

[0086] Test conditions: atmospheric pressure, mass space velocity WHSV = 30,600 mL·h -1 ·g cat -1 The test temperature was kept at 800°C. The catalyst activity was measured by CH4 conversion (X CH4 ) and CO2 conversion rate (X CO2 ) indicates the CH4 conversion rate (X CH4 ) and CO2 conversion rate (X CO2 ) is calculated as follows:

[0087] X CH4 =([CH4] in -[CH4] out ) / [CH4] in *100%

[0088] Where [CH4] in and [CH4] out are the contents of CH4 in the raw gas and the reaction tail gas respectively;

[0089] X CO2 =([CO2] in -[CO2] out ) / [CO2] in *100%,

[0090] Where [CO2] in and [CO2] out are the CO2 contents in the raw gas and reaction tail gas respectively.

[0091] according to Figure 5From the test results, we can observe that when the test temperature is 800°C, Example 2 exhibits good catalytic performance, with a methane (CH4) conversion rate of up to 90% and a carbon dioxide (CO2) conversion rate of 60%. These high conversion rate data are significantly better than the performance of other examples. These results suggest that it is necessary to conduct stability tests on it to verify its performance stability over a long period of time. The stability of Example 2 is more than 100 hours. In addition, Example 2 also has a characteristic that the hydrogen-to-carbon ratio (H2 / CO) is about 2, which makes it a promising candidate material for the preparation of biomethanol.

[0092] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A biogas dry and wet dual catalyst, characterized in that: Porous MgO is used as a carrier, Ru is loaded on the porous MgO, and the loading amount of Ru is 0.21wt%; the preparation method of the biogas dry-wet dual-process catalyst comprises the following steps: S1: a ruthenium source, a magnesium source and a soft template source are mixed and ground for 2 to 12 hours to obtain a precursor; the ruthenium source is one or more of ruthenium chloride, ruthenium acetate or ruthenium acetylacetonate; the magnesium source is one or more of magnesium acetate or magnesium nitrate; the soft template source is one or more of hexadecyltrimethylammonium bromide, polyether, polyetherimide or polyvinylpyrrolidone; S2: calcining the precursor at 500-700°C for 4-6 h in an oxygen-containing atmosphere to obtain a biogas dry-wet dual-process catalyst.

2. The biogas dry-wet dual-process catalyst according to claim 1, characterized in that: The mass ratio of the soft template source to other precursor salts in the catalyst is 0.1-0.5:

1.

3. The biogas dry-wet dual-stage catalyst according to claim 1, characterized in that: The grinding is ball milling.

4. The biogas dry-wet dual-process catalyst according to claim 1, characterized in that: The oxygen-containing atmosphere is an air atmosphere.

5. The biogas dry and wet dual-stage catalyst according to claim 1, characterized in that: The method also includes reducing and activating the biogas dry-wet dual-process catalyst prepared in step S2 at 600-800° C. in a hydrogen atmosphere.

6. Use of the biogas dry-wet dual-processing catalyst according to any one of claims 1 to 5 in catalyzing the conversion of biogas dry-wet dual-processing into synthesis gas.

Citation Information

Patent Citations

  • Methane dry reforming catalyst, preparation method and use of methane dry reforming catalyst and method for preparing synthetic gas through methane dry reforming

    CN105561998A

  • Ammonia decomposition catalyst and preparation method and application thereof

    CN113289693A